Analisis Kreatifitas Kelompok Masyarakat Menghadapi Kondisi Ekonomi Rumah Tangga - Novita, Novita (Komunitas Manajemen Kompetitif, 2016)
word creativity often we understand as an alternative and new innovations in human do when experiencing problems in dealing with problems. Creativity is also referred to as alternative work simplification so that it can produce a better product. Many definitions of creativity being addressed in accordance with permasalahnyaan. Housewife became one of the victims in the face of economic conditions, operationally housewife is a manager who manages the household finances and the need to provide creative art in optimizing the household expenses. De Jong & Den Hartog (2003) also describes the stages of creative behaviors innovative in making the innovation process into four phases as follows: see opportunity, issuing idea, fight for and application results showed quite good, especially in terms of the opportunities and put out the idea, but still low in the fight for the chance to become applicable in the field. Keywords: Creativity, Housewife